EVALUASI MODEL CIPP PADA PROGRAM PENDIDIKAN INKLUSIF DI SD - Ernawati, Ernawati; Rasyid, Muhammad Nur Akbar; Mania, Sitti (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This study aims to evaluate the inclusive education program at SD Negeri 2 Malino using the CIPP (Context, Input, Process, Product) model for comprehensive analysis. Data collection involved observation, interviews with the principal, teachers, students, and documentation studies, which were analyzed qualitatively with data triangulation. The results of the context evaluation showed that this program is strategic for expanding access to education and increasing public awareness and acceptance of diversity, despite being constrained by facilities and training. The input evaluation identified various supporting factors for program implementation. The process evaluation found that program implementation still requires increased consistency and effectiveness. Meanwhile, the product evaluation showed an increase in students, but the assessment and reporting system for students with special needs needs to be improved. Recommendations proposed include improving government policies and commitments, training human resources for the preparation of accommodative curricula and Individual Learning Plans (RPI), improving supporting facilities, developing a more flexible curriculum, improving the assessment and reporting system, and strengthening periodic program monitoring and evaluation by trained supervisors. ABSTRAKPenelitian ini bertujuan mengevaluasi program pendidikan inklusi di SD Negeri 2 Malino menggunakan model CIPP (Context, Input, Process, Product) untuk analisis komprehensif. Pengumpulan data melibatkan observasi, wawancara dengan kepala sekolah, guru, siswa, serta studi dokumentasi, yang dianalisis kualitatif dengan triangulasi data. Hasil evaluasi konteks menunjukkan program ini strategis untuk memperluas akses pendidikan dan meningkatkan kesadaran serta penerimaan masyarakat terhadap keberagaman, meskipun terkendala fasilitas dan pelatihan. Evaluasi input mengidentifikasi berbagai faktor pendukung pelaksanaan program. Evaluasi proses menemukan bahwa pelaksanaan program masih memerlukan peningkatan konsistensi dan efektivitas. Sementara itu, evaluasi produk menunjukkan adanya peningkatan pada peserta didik, namun sistem penilaian dan pelaporan bagi siswa berkebutuhan khusus perlu disempurnakan. Rekomendasi yang diajukan meliputi peningkatan kebijakan dan komitmen pemerintah, pelatihan sumber daya manusia untuk penyusunan kurikulum akomodatif dan Rencana Pembelajaran Individual (RPI), peningkatan fasilitas pendukung, pengembangan kurikulum yang lebih fleksibel, perbaikan sistem penilaian dan pelaporan, serta penguatan monitoring dan evaluasi program secara berkala oleh pengawas terlatih.